Constructive description of finite nondispersed groups where all subgroups of the nonprimary index are Abelian - Chernikov , S. N.; Levishchenko , S. S. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A theorem which provides a constructive description of finite nondispersive groups in which all subgroups of composite index are Abelian is proved.